KAJIAN DESAIN PERBAIKAN TANAH DASAR LUNAK MENGGUNAKAN GEOTEKSTIL DALAM PEMBANGUNAN INFRASTRUKTUR KAWASAN PARIWISATA MANDALIKA - Ari Ardiansah; Bagus Widhi Dharma S.; Aminullah Aminullah (SOSIAL SAINS DAN TEKNOLOGI, 2021)
Infrastructure development in the Mandalika tourism area has technical problems in the form of a thick layer of soft soil, so it is necessary to study the use of the geotekstile method as a development solution on soft soil. The geotekstile method is one of the materials technology methods used with polymer-based materials, which is very useful in solving problems related to soil stability and preventing uneven subsidence. The research objective was to determine the impact of the use of geotekstile in increasing soil stability, and to analyze road stability with geotekstile and without geotekstile using the study research method.The results of the study show that the construction of roads on soft soil, using geotekstile reinforcement, can increase soil stability so as to avoid local collapse. Soil study with geotekstile and without geotekstile, there is an ITP value of 12, Total Settlement using geotekstile of 67.8 cm while without geotekstile is 76.5 cm, Differential Sett on pavement using geotekstile is 5.9 cm while without geotekstile is 7.9 cm, Safety Number (SF) uses geotekstile amounting to 2.7 while without geotekstile of 1.3 and the volume of lost pile using a geotekstile of 47,000 m³ while without geotekstile of 47,500 m³